Amyloid-related imaging abnormalities associated with immunotherapy in Alzheimer's disease patients. (July 2012) - Panza, Francesco; Frisardi, Vincenza; Imbimbo, Bruno P; Logroscino, Giancarlo; Seripa, Davide; Pilotto, Alberto; Solfrizzi, Vincenzo
Evaluation of: Sperling R, Salloway S, Brooks DJ et al. Amyloid-related imaging abnormalities in patients with Alzheimer's disease treated with bapineuzumab: a retrospective analysis. Lancet Neurol. 11(3), 241–249 (2012). Amyloid-related imaging abnormalities (ARIAs) have been reported in patients with Alzheimer's disease treated with bapineuzumab, a monoclonal antibody targeting β-amyloid (Aβ). The spectrum of ARIA includes signal hyperintensities on fluid attenuation inversion recovery sequences thought to represent 'vasogenic edema' and/or sulcal effusion (ARIA-E), as well as signal hypointensities on gradient echo/T2 * thought to represent hemosiderin deposits. This study was a retrospective analysis in which two neuroradiologists independently reviewed 2572 fluid attenuation inversion recovery MRI scans from 262 participants in two Phase II studies of bapineuzumab and an open-label extension study. In this analysis, several ARIA-E cases were identified that were initially missed in the reported studies of bapineuzumab (42%). Associated clinical symptoms were observed in only 22% of patients with ARIA-E. Occurrence of ARIA-E increased with bapineuzumab dose and presence of apolipoprotein E (APOE) ε4 alleles. The increased risk of ARIA-E in APOE ε 4 carriers and the knowledge that vasogenic edema and microhemorrhages may spontaneously occur in cerebral amyloid angiopathy suggest a potential relationship with vascular Aβ burden. The increased risk of ARIA with a high bapineuzumab dose and the findings from a case with PET amyloid imaging also suggest a possible relationship between ARIA-E with Aβ clearance after passive immunotherapy with monoclonal antibodies.